2019
DOI: 10.3390/su11184931
|View full text |Cite
|
Sign up to set email alerts
|

Crop Production Pushes up Greenhouse Gases Emissions in China: Evidence from Carbon Footprint Analysis Based on National Statistics Data

Abstract: The rapid growth of crop yield in China was maintained by more fossil fuel inputs in the past years, causing concern about the greenhouse gas (GHG) emissions related to crop production. Therefore, this study analyzed historical dynamics of carbon footprint (CF) of 11 major crops in China during 2000–2016 and estimated possible GHG emissions of the system in 2020 under different scenarios. Results indicated that the GHG emissions of the Chinese crop system increased by 20.07% from 2000 to 2016, in which the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Our study presents a spatially explicit carbon footprint map for wheat and maize production at the county level in China. The mean GHG emission intensity of wheat and maize in our study is estimated at 0.56 (25 and 75% range: 0.50–0.73) kg CO 2 e kg –1 and 0.40 (0.36–0.56) kg CO 2 e kg –1 , respectively, which fall in the range of previous estimates ,, but are on the lower end (Figure ). These previous studies were at the national or provincial level.…”
Section: Discussionsupporting
confidence: 56%
“…Our study presents a spatially explicit carbon footprint map for wheat and maize production at the county level in China. The mean GHG emission intensity of wheat and maize in our study is estimated at 0.56 (25 and 75% range: 0.50–0.73) kg CO 2 e kg –1 and 0.40 (0.36–0.56) kg CO 2 e kg –1 , respectively, which fall in the range of previous estimates ,, but are on the lower end (Figure ). These previous studies were at the national or provincial level.…”
Section: Discussionsupporting
confidence: 56%
“…During crop production, cleaner technologies, which improve agricultural productivity and the efficiency of agricultural machinery operations [59] , can achieve the goals of GHG emissions reduction. At the same time, previous researches [30,60] pointed out that adjustment of crop planting structure is also an effective way to reduce GHG emissions. So this study attempts to use this idea in HLRA.…”
Section: 35mentioning
confidence: 99%
“…Most previous studies showed that carbon footprint was an effective indicator to develop cleaner agricultural technologies at the operational level. Meanwhile, improving crop planting structure would be also an important way to reduce GHG emissions [30] . At present, researches related to crop planting structure optimization through carbon footprint remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The total amount of GHGs produced by agricultural systems was 5.41 billion tons [1], accounting for approximately 14% of the total global GHGs [2]. A large number of studies have demonstrated that the excessive application of nitrogen fertilizer was the primary cause of GHG emissions from agricultural systems [3,4]. China is the largest producer and consumer of nitrogen fertilizer in the world.…”
Section: Introductionmentioning
confidence: 99%